Exploring the labor market consequences of psychiatric disorders: An event study approach - Salokangas Henri (Aboa Centre for Economics, 2022)
Vast literature documents a negative association between mental disorders and labor market performance but it is challenging to find a research design that could provide an reliable estimate for an effect. This paper provides new evidence on the immediate labor market consequences following the first psychiatric admission using the event study framework. To reduce selection bias, I exploit variation in the timing of the first psychiatric admission to estimate the effect of the first psychiatric treatment on labor market performance. Using Finnish administrative data, I find that the first psychiatric admission leads to loss in earned income of about AC1700 (10%). However, but to a large extent the empirical analyses demonstrate decreasing pre-trends in labor market outcomes before the event year, thus signaling problems related to endogeneity. Anxiety disorders provide a notable exception by exhibiting pre-event labor market trajectories for which parallel trends assumption cannot be ruled out. This study provides evidence that research designs that use timing variation in the first health may produce very modest pre-trends also in relationships typically considered endogenous.